Democracy and Economic Development in Nigeria from 1960 to 1999 - Nwokeke, Peter Osinakachukwu (2011)
This research examines democracy and economic development in Nigeria between 1960 and 1999. It discusses various democracies in Nigeria and various economic development efforts, including some of the shortcomings in their implementations. It also discusses the relationship between democracy and economic development. It is qualitative research which uses historical/content analysis to descriptively analyze both civilian and military regimes as they affected democracy and economic development in the country via secondary data collected from books, journals, magazines, newspapers and government reports. The importance of this research is to help policy makers in carrying out policies that will strengthen the standard of living of Nigerian citizens, to improve leadership iii qualities and good governance which will foster and consolidate democratic values and economic development in the nation. Evidences from findings show that democracy and the economy have failed to triumph in Nigeria due to reasons emanating from corruption, bad governance, lack of democratic values and wrong economic policies. This research contends that Nigerian democracy and economy have failed to develop because both economic and democratic policies are influenced by the West and this made this work adopted dependency theory. We are of the view that if all the findings in this work are properly put into cognisance by the Nigerian policy makers, it will go a long way in sustaining democratic values and economic development in Nigerian states.